2015
DOI: 10.1093/bioinformatics/btv715
|View full text |Cite
|
Sign up to set email alerts
|

destiny: diffusion maps for large-scale single-cell data in R

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
415
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(424 citation statements)
references
References 6 publications
9
415
0
Order By: Relevance
“…http://dx.doi.org/10.1101/363051 doi: bioRxiv preprint first posted online Jul. 7, 2018; maps 18 (Fig. 3d) or t-Distributed Stochastic Neighbor Embedding 19 (tSNE; Fig.…”
Section: Putative Transitions Between Myeloid Cell Clusters Suggest Pmentioning
confidence: 99%
See 2 more Smart Citations
“…http://dx.doi.org/10.1101/363051 doi: bioRxiv preprint first posted online Jul. 7, 2018; maps 18 (Fig. 3d) or t-Distributed Stochastic Neighbor Embedding 19 (tSNE; Fig.…”
Section: Putative Transitions Between Myeloid Cell Clusters Suggest Pmentioning
confidence: 99%
“…We therefore approached this question looking at indirect evidence, and in particular the existence of intermediate states between the identified B cell subsets. Projecting the gene expression data of the B cells onto 2 dimensions using diffusion maps 18 , we found that the naïve (CB2a) and . CC-BY-NC-ND 4.0 International license It is made available under a was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Indirect Evidence For B Cell Activation and Differentiation mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several computational methods have been reported that profile developmental processes, such as Monocle (Trapnell et al 2014), Wanderlust (Bendall et al 2014), Wishbone (Setty et al 2016), SLICER (Welch et al 2016), Diffusion Pseudotime , Destiny (Angerer et al 2016), and SCUBA (Marco et al 2014). These methods attempt to order cells into smooth continuous spatiotemporal trajectories to model development.…”
mentioning
confidence: 99%
“…(Pierson and Yau, 2015) or weighted gene co-expression network analysis (Langfelder and Horvath, 2008) are first used to project highdimensional data into a smaller number of dimensions to ease visual evaluation and interpretation. Clusters of similar cells can be identified using generally applicable methods, such as Gaussian mixture modeling (Fraley and Raftery, 2002) or K-means clustering, or methods devised specifically for single cell data, such as StemID (Grün et al, 2016), SCUBA, SNN-Cliq (Xu and Su, 2015), Destiny (Angerer et al, 2015) or BackSpin (Zeisel et al, 2015). Clusters can then be annotated based on domain-specific knowledge of the expression of a few genes, or automatically based on gene set enrichment.…”
Section: The Basics Of Scrna-seq Analysismentioning
confidence: 99%